2001
DOI: 10.1016/s0022-5347(05)65986-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Independent Risk Factors for Erectile Dysfunction in Spain: Results of the Epidemiologia De La Disfuncion Erectil Masculina Study

Abstract: This study provides data on the prevalence of and risks factors for erectile dysfunction in Spain. The relationship of erectile dysfunction with certain risk factors, such as cardiovascular risk factors and drugs intake, are well known and our study corroborates these associations. Other associations with erectile dysfunction, such as prostate disease, allergy and rheumatism, support findings in previous reports, although to our knowledge the pathophysiological mechanisms remain unclear. Estimating the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
270
6
32

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(323 citation statements)
references
References 16 publications
15
270
6
32
Order By: Relevance
“…All of these conditions contribute to erectile dysfunction, and in men with diabetes, the risk of erectile dysfunction is approximately four-fold higher than in men without diabetes [2,3]. Erectile dysfunction in men with diabetes is also more severe and less responsive to therapy than in men without diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
“…All of these conditions contribute to erectile dysfunction, and in men with diabetes, the risk of erectile dysfunction is approximately four-fold higher than in men without diabetes [2,3]. Erectile dysfunction in men with diabetes is also more severe and less responsive to therapy than in men without diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lukacs et al 11 surveyed a cohort of 6000 males with LUTS and found that a patient's sexual dysfunction was related to both age and LUTS severity. In a cohort of 2476 Spanish men, Martin-Morales et al 12 found that the prevalence of ED increased from 8.5% in men 35-39 years old to 48% in men 60-70 years old, as assessed by the International Index of Erectile Function (IIEF). Furthermore, LUTS was found to be the strongest independent risk factor for ED, with an age-adjusted odds ratio (95% confidence interval) of 2.67 (1.48-4.80).…”
Section: Introductionmentioning
confidence: 99%
“…6 According to the EDEM (Epidemiologia de la Disfuncion Erectil Masulina) study, subjects with prostatic disease have a 2.9 and 2.7 times higher probability (OR) of developing ED than male subjects from the general population as measured by a Single Assessment Question and the Erectile Function Domain of the International Index of Erectile Function (IIEF), respectively. 7 Furthermore, the EDEM study detected and quantified a strong association between lower urinary tract symptoms, measured with the International Prostate Symptom Score (IPSS), and the likelihood of developing ED, measured with the Erectile Function Domain of the IIEF. 8 Taking subjects aged between 25 and 39 years with mild symptoms on the IPSS as a reference category, the risk of developing ED increases more than two-fold if urinary symptoms are moderate and more than three-fold if symptoms are severe in any of the age groups (Table 1).…”
Section: Introductionmentioning
confidence: 99%